Ovarian cancer screening in the general population: current status. (1st July 2001) - Menon, U.; Jacobs, I. J.
Abstract : There has been considerable interest in the prospect of early detection of ovarian cancer through screening asymptomatic women from the general population. The results of recently published trials provide encouraging data on the possible impact on mortality. There are, however, concerns about compliance, cost, and morbidity from surgery for false positive screen results. The two ongoing randomized controlled trials in the US and UK aim to establish definitively the true impact of screening on ovarian cancer mortality while comprehensively tackling the issues of target population, compliance, health economics, and physical and psychological morbidity of screening.